Prediction of Fatigue Life on Lower Suspension Arm Subjected To Variable Amplitude Loading - M. M., Rahman; M. M., Noor; K., Kadirgama; R. A., Bakar; Z., Husin (2010)
This paper focuses on the finite element based fatigue life prediction of lower suspension arm, subjected to variable amplitude loading. The objectives of this study are to predict fatigue life of the lower suspension arm using stress-life and strain-life methods, to investigate the effect of the mean stress. The lower suspension arm was developed using computer aided design software. The finite element modeling and analysis were performed utilizing the finite element analysis code. Mesh was created using tetrahedral 10 nodes element. The finite element analysis then was performed using MSC.NATRAN code using the linear elastic approach. In addition, the fatigue life was predicted using the stress-life and strain-life approach subjected to variable amplitude loading. The three types of variable amplitude are considered in this study. The TET10 and maximum principal stress were considered in the linear static stress analysis and the critical location. From the fatigue analysis, Goodman method is conservative method when subjected to SAETRN and SAESUS loading histories while SWT method is more conservative in SAEBKT loading histories. Stress-life method is capable to give higher fatigue life when subjected to bracket mean loading (SAEBKT) while strain-life method is capable to give higher fatigue life when subjected to positive mean loading (SAETRN) and negative mean loading (SAESUS). From the material optimization, 7175-T73 aluminum alloy is suitable material of the suspension arm.